EDUCATION THE EFFECTIVENESS OF CARRYING DIDACTIC GAMES - S. Asqarova (American Journals, 2024)
This article will talk about educational games, the effect of educational games on the process of training, their use as a target, stages in the application of educational games, games that contribute to the mental development of the student.
Keywords: Educational games, method-forms, stages of Educational Games, groups of games.